Structure changes in InP and GaAs crystals double irradiated with electrons and swift heavy ions - Didyk, A.; Komarov, F.; Vlasukova, L.; Yuvchenko, V.; Bogatyrev, Y.; Korshunov, F.; Gracheva, E. (Вопросы атомной науки и техники, 2007)
We have studied InP and GaAs crystal structure changes under the influence of swift Kr and Bi ions irradiation by means of scanning electron microscopy, atomic force microscopy and selective chemical etching. The previous disordering of samples by electron irradiation is shown to be leading to macrodefect formation in the form of cracks and breaks at the depths near the ion end-of-range and on the crystal surface. A possible explanation of the observed effects is proposed. Вивчено вплив змін структури ІnP і GaAs при опроміненні іонами Kr і Bі й електронами при вивченні методом електронної мікроскопії, атомної силової мікроскопії й сективного хімічного травлення. Основними ефектами при цьому впливі були утворення тріщин і руйнувань структури поверхні, які найбільше значно проявлялися наприкінці пробігу іонів і поблизу поверхні. Можливе пояснення виявлених ефектів представлено. Изучено влияние изменений структуры InP- и GaAs- при облучении ионами Kr и Bi и электронами при изучении методом электронной микроскопии, атомной силовой микроскопии и сективного химического травления. Основными эффектами при этом воздействии являлись образование трещин и разрушений структуры поверхности, которые наиболее значительно проявлялись в конце пробега ионов и вблизи поверхности. Возможное объяснение обнаруженных эффектов представлено.